Migration Gravity, Networks, and Unemployment - Arnab K. Basu; Nancy H. Chau; Gary C. Lin (Institute of Labor Economics (IZA), 2022)
We develop and estimate a theory-consistent gravity model for interregional migration flows in the presence of unemployment. Micro-founded in a setting where search friction regulates labor market transitions, we derive a migration gravity equation for bilateral mobility that embodies a co-determined local unemployment term. As a theory of migration, our model connects directly with longstanding migration puzzles (e.g. declining internal mobility) as well as more novel concepts (e.g. home bias). As a model of unemployment, a migration gravity approach uncovers hitherto under-appreciated interregional roots of local unemployment, and furnishes an unemployment sufficient statistic interpretation to the familiar multilateral migration resistance term. We empirically test the predictions of the model using U.S. county-level data on bilateral migration and unemployment rates, bilateral connectedness data such as Facebook friendship links, and instrumental variable identification based on a novel similarity index of counties' historical ethnic-composition.
Keywords: J61; J64; R23; 330; friendship networks; gravity equation; internal migration